Perencanaan Rekrutmen Tenaga Pendidik di SMA Nurul Iman Palembang - Miranti, Mia; Setyaningsih, Kris; Atika, Nyimas (Indo-MathEdu Intellectuals Journal, 2025)
Planning for Recruitment of Educating Personnel is the process of planning and organizing the withdrawal steps carried out by educational institutions to meet the needs of teaching staff who have potential and broad insight in educational science and fulfill the terms and conditions that apply in educational institutions. This research is very important to ensure schools have qualified teaching staff that meet their needs. This research aims to find out how to plan the recruitment of teaching staff at SMA Nurul Iman Palembang, what are the obstacles and solutions to planning the recruitment of teaching staff at SMA Nurul Iman Palembang. This research uses qualitative research methods through a qualitative descriptive approach using interview, observation and documentation data collection techniques. The data analysis techniques used in this research are data reduction, data display and data verification. Meanwhile, in testing the validity of the research data, source triangulation and technical triangulation were used. The research results show that planning for the recruitment of teaching staff at SMA Nurul Iman Palembang has gone well. However, there are several obstacles related to planning the recruitment of teaching staff, namely a small operational budget which hinders the recruitment process, as well as compensation that is greater than other schools.